Pengaruh Kualitas Produk, Gaya Hidup, dan Pengetahuan Produk Terhadap Proses Keputusan Pembelian Sepeda Lipat di Kota Semarang - Yusuf Bagus Prakosa; Endang Tjahjaningsih (Forum Inovasi Bisnis dan Manajemen, 2021)
This study aims to analyze the effect of product quality on the purchasing decision process, the influence of lifestyle on the purchasing decision process and the influence of product knowledge on the folding bicycle purchase decision process in Semarang City. This research was conducted from November to December 2020 with the number of samples used as many as 100 respondents with the sampling technique in this study was purposive sampling. The data analysis technique used instrument test, model test, regression test using SPSS 24.0 software. The results showed that product quality, lifestyle, and product knowledge had a positive effect on the purchasing decision process. Product quality has the greatest influence on the purchasing decision process compared to lifestyle and product knowledge. The better the quality of the product, the higher the purchasing decision process.